The Frontline years : selected articles - Namboodiripad, E. M. S. (Leftword Books, 2010)
E.M.S. Namboodiripad is perhaps modern India's most important Marxist theoretician.//From 1992 till his death in 1998, EMS wrote a column in the newsmagazine Frontline. The present volume puts together a selection of his Frontline columns. This volume is a testimony to the variety of his interests, his erudition, and his ability to communicate complex questions of history and theory in simple and elegant prose.//EMS discusses, among other things, the roles and contributions of Congress leaders from Dadabhai Naoroji and Ranade to Gandhi, Subhas Bose and Nehru to Narasimha Rao and Manmohan Singh; he discusses the thoughts and relevance of Marxist theoreticians including Lenin, Rosa Luxemburg, Mao Tse-tung and Stalin, as well as Nelson Mandela; he writes on religion, philosophy and art; he discusses important questions of the Indian polity including planning and centre-state relations; he comments on the Indian Communist movement (including on the decision not to join the United Front government at the centre in 1996); and he writes about the radical experiments in Kerala.